Предупреждение преступлений на рынке эмиссионных ценных бумаг - Тогайбаева, Ш.С.; Тогайбаев, А.И. (Изд-во КарГУ, 2010)
Мақала эмиссиялық бағалы қағаздар рыногындағы қылмыстылықты алдын алу мəселелеріне арналған. Авторлар қылмыстылық түсінікті, оның алдын алу шараларын қарастырып, қылмыстық заңнаманы əрі қарай жетілдіру бойынша ұсыныстар жасайды. The article is devoited to the prevention of the crimes on the market of the securities.The authors consider causes and conditions the accomplishment of crimes on the market of the securities.The authors propose to establish the organ (who) which can watch for transaction shady.The authors express their s opinion about improving criminal legislation.